Dietary diversity is associated with nutrient adequacy, blood biomarkers and anthropometric status among preschool children in poor ethnic minority area of Northwest China - Hu, Binshuo; Tang, Shihua; Wang, Zhuo; Chen, Youhai; Chen, Xiaohui; Zhao, Qian; Jiang, Yu; Shen, Minghui; Zhang, Chong; Kaliszewski, Catherine; Wang, Liang; Zhang, Ying (Frontiers in Nutrition, 2022)
This study aimed to evaluate the status of dietary diversity, nutrient adequacy, blood biomarkers of nutrients, and anthropometric status as well as to explore the predictors of dietary diversity score (DDS) and mean adequacy ratio (MAR) among preschool children in poor ethnic minority areas of northwest China. A total of 578 healthy preschool children aged 3-6 from 17 kindergartens were selected to assess dietary intake, anthropometric status (height-for-age z-score (HAZ), weight-for-age z-score (WAZ), weight-for-height z-score (WHZ), and blood biomarkers. DDS and nutrient adequacy ratio (NAR) were adopted to assess dietary diversity and micronutrient adequacy, respectively. The mean DDS (range from 1 to 9) was relatively low (4.67 ± 1.56). Most participants consumed starchy staples, but few participants consumed organ meat. DDS was associated with serum potassium, serum iron, WAZ, HAZ, all NARs, and MAR (p < 0.05). Living in urban areas, higher household wealth, not engaging in farming, and more caregivers’ nutritional knowledge were positively associated with DDS while living in urban areas, higher education of caregivers, and higher DDS were positively associated with MAR. In conclusion, dietary diversity was associated with nutrient adequacy and other health outcomes. Nutritional education and poverty alleviation are integral to improving the nutritional status of preschool children.